Generic stacks and application of composite rules for the detailed sizing of laminated structures. (15th November 2021) - Ntourmas, G.; Glock, F.; Daoud, F.; Schuhmacher, G.; Chronopoulos, D.; Özcan, E.
Abstract: Two-stage approaches are commonly applied to optimise the stacking sequence of large-scale composite structures. The two stages consist of a gradient and non-gradient based optimisation addressing the mixed nature of continuous and discrete constraints and design variables of the detailed sizing of laminated structures. For the two-stage process to be successful, all constraints from both stages should be fulfilled eventually. This study employs generic stacks to model the thickness and stiffness distribution of the structure. A generic stack is comprised of a collection of layers whose orientations are fixed a priori, but thicknesses can vary independently enabling exploration of the design space. To achieve a 'right first time' implementation and avoid burdensome iterations over both stages, a maximum amount of discrete design and manufacturing constraints should be considered in the gradient-based optimisation stage. A special attention is paid to the continuity or blending constraint which can be formulated precisely using generic stacks. The results for a benchmark case show that the introduced two-stage approach can, not only satisfy all imposed constraints in a single iteration of the overall two-stage process but also yield a lower structural mass when compared to equivalent previously proposed approaches.